Operation mode of phase modulation based on carrier dispersion effect in p-i-n diode of silicon rib waveguide - Mardiana, Bidin; Haroon, Hazura; Hanim, Abdul Razak; Menon, P.S; Abdullah, H. (2010)
This paper highlights the study of the carrier injection mode and the carrier depletion mode of the phase modulator. The phase modulator device has been integrated in the silicon rib waveguide by using the p-i-n diode structure. The electrical device performance is predicted by using the 2-D semiconductor package SILVACO (CAD) software under DC operation. Summarily, the phase modulator device has less sensitivity to the effective refractive index changes when operating in reverse biased or depletion mode compared to the forward biased or injection mode.